My heart - Furgang, Kathy (New York : Rosen Pub. Group's PowerKids Press, 2000)
This book describes the parts, activities, and functions of the human heart and circulatory system and problems that may develop there.
Includes index.
Includes glossary.
K-3
Accelerated Reader AR
Keywords: Heart; Cardiovascular system